2020
DOI: 10.48550/arxiv.2005.11106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the suitability of generalized regression neural networks for GNSS position time series prediction for geodetic applications in geodesy and geophysics

Abstract: In this paper, the generalized regression neural network is used to predict the GNSS position time series. Using the IGS 24-hour final solution data for Bad Hamburg permanent GNSS station in Germany, it is shown that the larger the training of the network, the higher the accuracy is, regardless of the time span of the time series. In order to analyze the performance of the neural network in various conditions, 14 permanent stations are used in different countries, namely,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The GP algorithm is the most accurate machine learning method, since it has the lowest values of mean(RM SE) and M ASE. On the other hand, as [4] also asserts, the RBF algorithm is the least accurate method. Once again it is confirmed that the RBF algorithm is not suitable for the GNSS position time series prediction.…”
Section: Explanation Of the Algorithmmentioning
confidence: 93%
See 2 more Smart Citations
“…The GP algorithm is the most accurate machine learning method, since it has the lowest values of mean(RM SE) and M ASE. On the other hand, as [4] also asserts, the RBF algorithm is the least accurate method. Once again it is confirmed that the RBF algorithm is not suitable for the GNSS position time series prediction.…”
Section: Explanation Of the Algorithmmentioning
confidence: 93%
“…• Use of time series in different atmospheric and tidal conditions. We use the same choice of stations in [4], which are taken from [28]. Hence, based on the points mentioned above, the following table represents the result of applying the algorithm (and its aiding machine learning algorithms) to the permanent GNSS stations mentioned in .…”
Section: Explanation Of the Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning prediction algorithms are increasingly gaining attention in the field of geoscience [1], [2]. These methods are different from the traditional, statistical methods for approximation and interpolation [4]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning algorithms are even more powerful than the statistical methods such as Theta [3] for prediction purposes [1], [2]. In [1], an analysis for the efficiency of the Generalized Regression Neural Networks (GRNN) for the prediction of GNSS time series values is presented.…”
Section: Introductionmentioning
confidence: 99%